Cytological features of non-small cell carcinomas of the lung in fine needle aspirates. - Zusman-Harach, S B (1991)
Fifty eight lung tumours were typed according to the second World Health Organization histological classification and compared with the cytological appearances obtained by fine needle aspiration in a total of 47 primary non-small cell carcinomas. The presence of glands, cell balls, branching or papillary structures, cylindrical cells and nuclear grooving were major diagnostic indicators for adenocarcinoma. Cytoplasmic macrovacuoles were more common in adenocarcinomas (69%) than in squamous (37%) and large cell (50%) carcinomas. Two or more of these features were combined in all well and moderately differentiated adenocarcinomas and in 67% of poorly differentiated adenocarcinoma. The major cytological indicators for squamous carcinomas were the presence of keratin and eosinophilic spindle cells with glassy or laminated cytoplasm. Granular cytoplasm was not specific for any histological type. A combination of the major features for both adeno- and squamous carcinoma was present in 58% of adeno-squamous carcinomas, including some poorly differentiated types. Correct typing could be obtained in almost all the well and moderately differentiated carcinomas and in about two thirds of the poorly differentiated tumours using FNA, provided that combinations and not individual variables are considered.